Competitive Growth of Nitrosomonas and Nitrobacter in Inorganic Sulfur Containing Sandy Soils - SALEH, S. M. (The Libyan Journal of Agriculture, 2023)
Growth of Nitrosomonas was competitively inhibited by zymogenously growing T. thioparus and other sulfur bacteria in soils containing 640 ppm thiosulfate-S. Nitro-* somonas was, therefore, recovered in numbers as low as 100 cells/g soil within 16 days of incubation. Growth of Nitrobacter, however, was significantly enhanced by this treatment, and counts of about 9.1 x 10r* cells/g were thus obtained within 8 days of incubation. Incorporation of an equivalent amount of sulfur in the form of either elemental sulfur or diluted sulfuric acid, though did not show any effect on the activity of Nitrosomonas, both of these treatments had apparently stimulated the growth of Nitrobacter in soil.